The good Chinese lawyer : a student guide to law and ethics / Adrian Evans, Monash University; Richard Wu, The University of Hong Kong; Xu Shenjian, China University of Political Science and Law. - Evans, Adrian; Wu, Richard, 1962-; Shenjian, Xu, 1966- (Cambridge University Press, 2023)
The Good Chinese Lawyer explores the ethical and professional challenges that will confront a law student, and will help them to prepare for life as a lawyer. The book offers principled and pragmatic advice about how to overcome such challenges. It urges readers to examine motives for seeking a career in law, to foster a deep understanding of what it means to be 'good' lawyer, and how to draw on virtue and judgment when difficult choices arise, rather than simply relying on rushed compliance with rules or codes. The Good Chinese Lawyer analyses four important areas of legal ethics - truth and deception, professional secrets, conflicts of interest, and professional competence - and explains the choices that are available when determining a course of moral action. It links theory to practice, and includes many diagrams and scenarios to illustrate ethical concepts and good decision-making.